2012
DOI: 10.1016/j.afjem.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The pending loss of advanced life support paramedics in South Africa

Abstract: Background In 2008 South Africa (SA) had 1631 registered advanced life support (ALS) paramedics to provide pre-hospital advanced life support care to a population of approximately 50 million. Compared to globally accepted ratios, the number of ALS paramedics in South Africa can be considered as grossly inadequate. This current shortage may be ascribed to migration. However, the extent and nature of this migration, the factors that have contributed to them leaving the country and the existence or effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…[12] SA has been losing significant numbers of prehospital practitioners with advanced training over the past decade. [13] Poor working conditions, physical security and economic considerations were identified as some of the main 'push' factors. [13] Govender et al [14] also hinted that current measures are inadequate to actively manage the shortages of prehospital practitioners with advanced training and their migration out of SA.…”
Section: Prehospital Emergency Carementioning
confidence: 99%
“…[12] SA has been losing significant numbers of prehospital practitioners with advanced training over the past decade. [13] Poor working conditions, physical security and economic considerations were identified as some of the main 'push' factors. [13] Govender et al [14] also hinted that current measures are inadequate to actively manage the shortages of prehospital practitioners with advanced training and their migration out of SA.…”
Section: Prehospital Emergency Carementioning
confidence: 99%
“…There are proportionately lower numbers of registered prehospital emergency care personnel in these categories [ 20 ]. This is compounded by the numbers of advanced life support prehospital emergency care providers who leave the country to find work elsewhere [ 21 ]. There is usually a minimum clinical experience timeframe required for expatriate work, meaning that many higher qualified practitioners with experience have left the South African healthcare sector.…”
Section: Discussionmentioning
confidence: 99%
“…One of the negative consequences is the loss of skilled staff when qualified EMS personnel leave SA to practise abroad, where working and living conditions are believed to be safer. [9] In response to the abovementioned concerns, certain law enforcement agencies and EMS providers offer hostile environment awareness training (HEAT) programmes for their staff. [10] These HEAT programmes focus on developing one's ability to assess situations, recognise specific risk factors, and where possible avoid these risks.…”
Section: Researchmentioning
confidence: 99%
“…Exposure of paramedics to physical violence globally appears to vary considerably -from 2.9% to 79.5%. [3][4][5][6]9,14] Our literature review found few published studies that specifically dealt with the incidence of violence against EMS students. Of our 113 respondents, 78.76% reported being verbally abused (sworn at, ridiculed or threatened) either by a patient or bystander.…”
Section: Violence Against Emergency Medical Services Personnel and Stmentioning
confidence: 99%